Exploring Conjunctive Adverbials in International and National Indexed Journals - Avika Cahyowati (Universitas Pendidikan Indonesia (UPI), 2018)
This study explores the use of conjunctive adverbials (CAs) in journals with different indexing levels, specifically to see the distribution of conjunctive adverbials and whether the most dominant conjunctive adverbial is used correctly. Thirty articles were collected from two journals, with specification: fifteen articles from journal indexed in international database (INT) and fifteen articles from journal indexed in national database (NAT), and encoded into INT-01 until INT-15 and NAT-01 until NAT-15. Forty adverbials belonging to four classes of conjunctive adverbials according to Celce-Murcia and Larsen-Freeman (1999) were searched using Laurence Anthony’s concordance program (AntConc). The results show thirty individual conjunctive adverbials from four classes occur in the whole corpus. From this finding, additive class dominates the frequency of occurrence in the whole corpus by 49.4 percent. In line with this result, the most frequently used CA is the conjunctive adverbial also, with 26 percent occurrence from 1380 CAs found in the whole corpus. Based on these results, the analysis is centered on conjunctive adverbial also as the most dominant CA in order to see how this CA is used. The findings show that the conjunctive adverbial also is mostly used correctly; however, there are cases where the use of conjunctive adverbial also is redundant with additive class members, and even overlaps with other classes. In conclusion, the case of overuse and inappropriate register still linger on the use of CAs in academic prose register, whether it is internationally indexed or not. Keywords: research articles, journal indexation, conjunctive adverbials